Polynomials : please give a step by step solution

Asked by jayantkaushik | 6th Sep, 2009, 09:17: PM

Expert Answer:

6x3-11x2 = kx -20

x = 4/3

6(4/3)3-11(4/3)2 = k(4/3) -20

6(64/27) - 11(16/9) = k(4/3) - 20

6(64/27) - 11(3)(16/27) = k(4/3) - 20

(384 - 528)/27  = k(4/3) - 20

-144/27 = k(4/3) - 20

k =  11

Regards,

Team,

TopperLearning.

 

Answered by  | 6th Sep, 2009, 09:51: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.